A novel experimental model for studying transverse orthodontic tooth movement in the rat mandible - Alsagheer, A.; Kline, L.; Doschak, Michael; Major, P. (E H Angle Orthodontists Research & Education Foundation, Inc., 2013)
OBJECTIVES: To establish a rat model of a one-piece mandible using the principles of gingivoperiosteoplasty and guided bone regeneration to fuse the midline symphyseal area. MATERIALS & METHODS: Twenty-four Sprague-Dawley female rats were divided into two groups: 12 experimental and 12 control. Both groups were imaged using in vivo micro-computed tomography at baseline and at end point (5 months). The experimental group received regenerative surgery at the symphysis area; the control group received no treatment. Outcomes were evaluated by radiographic examination of gross and volumetric bony changes in the symphyseal region of interest marked between the mental foramina bilaterally and the two central incisors near the most coronal margin of the alveolar crests. These landmarks were chosen as they can be reproduced on the computed tomography images at baseline and end point. Histologic examination was performed on all samples at a level 5 mm apical to the alveolar bone crest. RESULTS: Radiologic and histologic examinations of the experimental group revealed complete bony fusion of the symphyseal area in three subjects, partial fusion in five subjects, and thickening of the alveolar bony socket in three subjects; one rat died of anesthesia-related complications. No evidence of fusion or alveolar bone thickening was found in any of the controls. CONCLUSIONS: This surgical animal model demonstrates that a rat mandible can be surgically manipulated to mimic the one-piece human mandible. This novel model may prove useful in studying mandibular bone remodeling and orthodontic mandibular tooth movement.